(3GdJYdje aj OhdI GdGeGQGJ GdYQHjI GdeJMOI(B:s (3adSaJg hCOhGQg hQDi GdJWhjQ GdeSJbHdjI (B/s - (3YhTI GdegjQjs ((3CHhXHj (B- (3OhdI GdGeGQJ GdYQHjI GdeJMOI(B:s (3eQcR GdGeGQGJ ddOQGSGJ hGdHMhK GdGSJQGJjLjI(B,s, 2022)
(3gPG GdcJGH GdoenMnqce gh HGchQI GdEfJGL GdeTJQc Hjf LGeYI GdEeGQGJ GdYQHjI GdeJMOI, heQcR GdEeGQGJ ddOQGSGJ hGdHMhK GdGSJQGJjLjI, hjJfGhd YOkOG ef Cge bVGjG GdJYdje Ydi GdUYjnOjf GdYGdej hGdeMdj; hbO TGQc aj JCdjag fNHI ef CSGJPI cdjI GdJQHjI aj GdLGeYI; hJhnqdJ EOGQI GdfT`Q GdYdej HGdeQcR JMQjQg heQGLYJg hJObjbg hJfajPg; djWQM CSFdI egnqeI aj eLGd GdJYdje, hjLjH YfgG; WGQkMG QkDi eJbOekI MjGdgG; hjbJQM SHd GdJWhjQ(B. (3hbO LGA gPG GdcJGH aj SJI aUhd; MjK GSJYQV GdaUd GdChd hGbY GdJYdje GdOGeL aj OhdI GdEeGQGJ GdYQHjI GdeJMOI, hCHQR GdUYhHGJ GdJj jhGLggG, hGdJMOjGJ GdeSJbHdnqjI, hSHd JWhjQg aj GdOhdI, eY GdJQcjR Ydi fgL hRGQI GdJQHjI hGdJYdje, eeKdkI aj EOGQI GdJQHjI GdNGUI, fMh eHOC GdJYdje GdOGeL(B. (3CeG GdaUd GdKGfj abO Cdbi GdVhA Ydi BdjGJ JWhjQ GdefGgL heQGMdg aj HYV GdOhd GdeJbOeI; ehVkMG CgenqjI JWhjQ GdefGgL aj GdYGde YehkeG, haj OhdI GdEeGQGJ GdYQHjI GdeJMOI Ydi hLg GdNUhU(B. (3hSYi GdaUd GdKGdK Edi JYoqQa S`jGSGJ JYdje GdehGWfI GdYGdejI hGSJQGJjLjGJgG ddNeS`jf YGkeG GdebHdI aj OhdI GdEeGQGJ, eY ELQGA ebGQfI Hjf GgJeGe GdfXGe GdJYdjej GdEeGQGJj, hHYV CfXeI GdJYdje aj Ohd eNJGQI, HLhGfH GdehGnWnfI GdYGdejI(B. (3hGSJbQC GdaUd GdQGHY eSJbHd GdJYdje, hGdJZoqjQGJ GdJj HRZJ NdGd GdSfhGJ GdCNjQI; QGSkeG HYV edGeM eSJbHd GdJYdje hab GdeYWjGJ GdeJGMI ef HMhK hOQGSGJ hedGMXGJ hGSJfJGLGJ(B. (3hLGA GdaUd GdNGeS djfGbT edGeM JWhjQ JYdje GddZI GdYQHnqjI aj VhA GdQDi GdeSJbHdnqjI dOhdI GdEeGQGJ GdYQHjI GdeJMOI, NGUI HYO EWdGb eFhjI GdEeGQGJ (B2071(3; dJhGcH Jdc GdefGgL JZoqjQGJ GdeSJbHd; hJhGLg JMOjGJg, hJdHj MGLGJg(B. (3hMGhd GdaUd GdSGOS, GdCNjQ, HdhQI QDjI hGVMI dJVejf GdefGgL GdOQGS`jI GJLGgGmJ MOjKkI heYGU`QkI JOYe GdghjI GdhWfjI hGdehGnWfI; hJhGcH SYj GdOhdI Edi JWhjQ fXGe JYdjej ef GdWQGR GdChd jbhO Edi JMbjb gOagG, GdeJeKd aj Cf Jchf Vef CaVd Ohd GdYGde Ydi LejY GdoqUoYO(B.s
Keywords: (3GdJYdje aj OhdI GdGeGQGJ GdYQHjI GdeJMOIs; (3GdJYdje h GdJhbYGJ GdeSJbHdjIs; (3GdJYdje (B- (3bQf (B21s; (3LhOI GdJYdjes; (3GdeYQaIs; (3JJWhjQ GdefGgLs; (3GdJNWjW GdJQHhjs